Enrichment: A Critique of Commodities (excerpts) - Boltanski, Luc; Esquerre, Arnaud (Journal of Economic Sociology, 2020)
The authors of this book argue that Western capitalism has recently undergone a fundamental transformation that especially apparent in those countries responsible fpr European industrial primacy. There are two significant dimensions of the work: historical and analytical. The first dimension focuses on economic changes that have been observed since the late 20th century and dramatically modified the way value and wealth are created today: on one hand, the transformation characterized by deindustrialization; and, on the other, the increased exploitation of certain resources that, while not entirely new, have taken on an unprecedented importance. The second direction aims to understand how different commodities can generate transactions perceived as normal by buyers and sellers and that fit preliminary expectations to a certain degree. From a theoretical perspective, the authors deliberate pragmatic structuralism that combines social history with the analysis of cognitive competences upon which actors rely. In terms of empirical data, the authors use statistics enriched with a set of various formal and informal interviews, focusing on France as a case where the mentioned transformation is more distinctive. The Journal of Economic Sociology publishes some excerpts from the second chapter “Toward Enrichment” where the authors define the main sources and benefits of the enrichment economy. The enrichment economy is based less on producing new objects and more on enriching existing things and places by connecting them with specific narratives.